The Flâneur in Baudelaire and Whitman - Huang, Chiung-Ying (International Journal of Language and Literary Studies, 2024)
This paper discusses the trans-cultural affinities between Whitman and Baudelaire through the question of the flâneur, a figure whose emergence coincides with the booming development of economic industry in the nineteenth century. Although there is no historical evidence that Whitman had any real connection with Baudelaire in his life, both Baudelaire and Whitman are all poets of modern life and have mutual infatuation with modernity. Both poets also innovatively demonstrate their poetic strength by establishing a poetic world dominated by visual images, with their poetic visions deeply rooted in the frank realities of modern urban life, unveiling a particular Modernist mode of urban experience. In investigating a possible link between Baudelaire and Whitman, this paper concludes that the relationship between the two poets is one of confluence rather than influence. Though deployed in the mode of the flâneur, Whitman’s poetics is in essence apart from this French model. More than simply a flâneur, Whitman is the poet of the city, the crowds, the body, the soul, and the nation. Discussing the roles of the flâneur in Whitman and Baudelaire, this paper manages to introduce new material for a comparative study between the two poets.